The Effect of Spiritual Self-Care Training on Feeling of Comfort in Mothers of Hospitalized Preterm Infants - Tayebe Reihani; Zohre Sekhavat Poor; Mohammad Heidarzadeh; Seyed Mehdi Mosavi; Seyed Reza Mazlom (Mashhad University of Medical Sciences, 2014)
Background and aim:  The stress resulting from premature delivery and the related neonatal care induces psychological and physical pressure on the mothers, and adversely affects their feeling of comfort. It seems that spiritual care as a sort of communication with a higher power (God) can bring peace to the stressed mothers, and prevent anxiety. Therefore, this study was designed to evaluate the effects of spiritual self-care training on feeling of comfort in mothers of preterm infants, hospitalized in the neonatal intensive care unit (NICU). Methods: In this randomized clinical trial, 60 mothers of preterm infants hospitalized in NICU of Omolbanin and Ghaem hospitals, Mashhad, Iran in 2013, were selected, using convenience sampling, and were randomly assigned to intervention and control groups. In order to familiarize the mothers with their infants' condition, the mothers in both intervention and control groups were informed and trained for 15 minutes every day, over a 14-day period. The intervention group, in addition to infant-related information, received spiritual self-care training for 45 minutes in 6 sessions, every other day. Before and after each session of self-care training, the mothers filled a self-structured questionnaire related to feeling of comfort resulting from spiritual care. Data were analyzed using SPSS version 16, by repeated measures analysis of variance (ANOVA), t-test, and Chi-square tests. Results: According to the results, the total mean of maternal feeling of comfort was 50.0 ± 4.3 and 55.6 ± 3.3 before and after the intervention, respectively. The results of t-test indicate that comfort significantly increased after the intervention (P=0.000). Conclusion: Based on the results of this study, spiritual self-care training increases the feeling of comfort in mothers with premature infants, hospitalized in NICU.